Advances in Smart Technologies for Structural Health Monitoring of Cable-stayed Bridges - Ho, Duc-Duy; Le, Thanh-Cao (Institut Teknologi Sepuluh Nopember, 2017)
This study deals with the general problem of developing smart technologies for vibration and impedance-based structural health monitoring (SHM) of cable-stayed bridges. The following approaches are implemented to achieve the objective. Firstly, vibration- and impedance-based SHM methods suitable for cable-stayed bridge are briefly outlined. Secondly, smart sensors are designed for vibration- and impedance-based SHM. Thirdly, the practicality of the smart sensor system is evaluated on a real cable-stayed bridge, Hwamyung Bridge in Korea. The system's performance is experimentally analyzed under various cable forces and weather conditions. Finally, the experimental modal parameters are identified by numerical modal analyses of the target bridge. Also, its structural parameters are estimated from the vibration-based structural identification using experimental modal parameters.